I see you've called in dead : a novel - Kenney, John, 1962- (Zibby Publishing, 2025)
"Bud Stanley is an obituary writer who is afraid to live. Yes, his wife recently left him for a 'far more interesting' man. Yes, he goes on a particularly awful blind date with a woman who brings her ex. And yes, he has too many glasses of Scotch one night and proceeds to pen and publish his own obituary. The newspaper wants to fire him. But now the company's system has him listed as dead. And the company can't fire a dead person. The ensuing fallout forces him to realize that life may be actually worth living. As Bud awaits his fate at work, his life hangs in the balance. Given another shot by his boss and encouraged by his best friend Tim, a worldly and wise former art dealer, Bud starts to attend the wakes and funerals of strangers to learn how to live"--